The Effect of the PQ4R Model Assisted by E-Book Application Sway Students' Scientific Literacy Excretion System Materials for Class XI MAN Palangka Raya City - Zaini, Achmad; Ayatusa'adah, Ayatusa'adah; Nirmalasari, Ridha (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
This research is based on learning conditions in class XI MAN Palangka Raya City which still uses discussion and lecture models that are less able to improve scientific literacy skills. This research aims to determine the effect of the PQ4R model assisted by e-books using the sway on the scientific literacy of XI grade students of MAN PalangkaRaya City in the matter of the excretory system. The design used in this research is in the form of a quasi-experimental and the form of the design is divided into 2 groups, namely the experimental group and the control group, also called the Non-equivalent Control Group Design, and uses descriptive quantitative calculations. The sample in this research has a total of 67 students which includes, XI MIPA 3 totaling 33 students in the experimental class, and XI MIPA 4 totaling 34 students in the control class.is purposive sampling. The scientific literacy data collection method was taken from the results of the scientific literacy test. The results of the research using an independent sample t-test analysis showed that there was an effect of the PQ4R model assisted by e-book application Sway on the scientific literacy of class XI MAN Palangka Raya students on the excretory system material with a value of tcount > ttable, which is 5,319 > 5,299 .learning model supported by the Sway e-book application PQ4R can improve scientific literacy.